Office 2016 for dummies - Wang, Wally (--For dummies., 2016)
Office 2016 For Dummies (9781119293477) was previously published as Office 2016 For Dummies (9781119077374). While this version features a new Dummies cover and design, the content is the same as the prior release and should not be considered a new or updated product. The bestselling Microsoft Office book of all time Packed with straightforward, friendly instruction, this updated edition of the bestselling Microsoft Office book gets you thoroughly up to speed on the latest version of the industry standard for office productivity suites. In no time, Office 2016 For Dummies will help you become a whiz at Word, take your Excel skills to new heights, add pizzazz to your PowerPoint presentations, and make every part of your work day more organized and productive. Following alongside approachable, plain-English explanations, you'll quickly discover how to type, format text, and design documents in Word; navigate and edit spreadsheets, create formulas, and analyze data in Excel; configure email, store contacts, organize tasks, and schedule your time with Outlook; create and edit well-designed and crowd-pleasing PowerPoint presentations; and design, edit, and modify an Access database. Even if the mere thought of working with Microsoft Office makes you nervous, this fun and friendly guide makes it easy. Helps you make sense of word processing, email, presentations, data management and analysis, and much more Covers the five main Office applications: Word, Excel, PowerPoint, Outlook, and Access Walks you through the new features of Microsoft Office 2016 Written by a veteran author who has written more than 20 For Dummies books, which account for more than three million books in print If you're an uninitiated user looking to make the most of this powerful suite of applications, this hands-on, friendly guide is the key to your brand new Office!